Reproductive features of the Antarctic silverfish (Pleuragramma antarctica) from the western Ross Sea - Ghigliotti L; Ferrando S; Carlig E; Di Blasi D; Gallus L; Pisano E; Hanchet S.; Vacchi M (Polar Biology, 2017)
The Antarctic silverfish Pleuragramma antarctica is the most abundant pelagic fish inhabiting the Ross Sea. Given its ecological relevance in the local food web, it is considered a keystone species in the Antarctic coastal ecosystems. Many aspects of its biology have been elucidated, but knowledge of important parts of its life cycle, including reproduction, is still poor. Here we use macroscopic and histological approaches to describe the reproductive features of the Antarctic silverfish based on fish sampled in late summer in the Ross Sea. Both males and females were at an early developmental stage, consistent with what has been reported for the same species from other Antarctic sectors and with spawning occurring in late winter. Widespread follicular atresia has been detected in the fish examined. The analysis of its intensity and prevalence suggests that skipped spawning (not all adults spawn every year) is likely to be a reproductive strategy of the Antarctic silverfish. © 2016 Springer-Verlag Berlin Heidelberg